Calculation of experimental apparatus for biological object irradiation by ultrawideband electromagnetic field - Думин, А. Н.; Шкорбатов, Ю. Г.; Чернов, А. И.; Катрич, В. А. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 1970)
The phenomena of homogeneous irradiation of biological solutions by impulse electromagnetic field is investigated. The optimization of construction and sizes of the apparatus for the irradiation is carried out by direct numerical calculation in time domain. Uniformity of heat distribution in solution is studied.